The Big Digital Contact Tracing Experiment. (19th June 2021) - de Bengy Puyvallée, Antoine; Storeng, Katerini Tagmatarchi
Abstract: Over a third of the world's countries have launched contact‐tracing apps in response to the COVID‐19 pandemic, generating much hype about the prospect of automating contact‐tracing to manage outbreaks and to alleviate costly and labour‐intensive 'manual' contact tracing. Despite the stringent scientific criteria applied to the development of vaccines and other 'biomedical countermeasures' in responding to the pandemic, digital contact tracing has been widely recommended despite being an unproven public health intervention. Evidence for its effectiveness is thin, based on theoretical mathematical modelling and unsystematic observations across diverse country contexts. Establishing evidence of effectiveness is complicated by the fact that two private corporations, Apple and Google, own the technology upon which most government contact‐tracing apps are based and which, by design, restricts access to needed data on privacy grounds. In this policy insight, we make the case for why public health authorities urgently need to establish the effectiveness and societal implications of this big digital contact‐tracing experiment. Abstract : We do not actually know if and how contact‐tracing apps, for example, perform relative to established 'manual' contact tracing systems (though there is growing evidence that they cannot replace them), or how digital technologies work in distinct health systems or social and political contexts.